Russia's turn to Persia orientalism in diplomacy and intelligence - Volkov, Denis V. (Cambridge University Press, 2018)
Iran has remained one of the most effective tools in Russia's foreign policy towards the West for more than two hundred years. Drawing on previously unpublished and recently declassified sources which change the established wisdom on many aspects of the history of Russia and Iran, Denis V. Volkov examines this relationship, and situates it within the broader context of Oriental studies. With a particular focus on the activities of scholars-diplomats, as well as scholars involved in academia, missionary activities and the military within their own professional domains, Volkov analyses the interaction of intellectuals with state structures and their participation in the process of shaping and conducting foreign policy towards Iran. This work explores the specific institutional practices of Russia's Oriental studies, including organisation of scholarly intelligence networks, taking advantage of state power for the promotion of institutional and individual interests, and profound engagement with Russia's domestic and foreign policy discourses of its time.